Um estudo sobre o uso de periódicos eletrônicos: O Portal De Periódicos CAPES na Universidade Federal de Minas Gerais - Luiz Claudio Gomes Maia (2005)
The focus of this dissertation is the study of the use of the Portal de Periódicos CAPES, a site that offers access to electronic journal articles, in practically all fields of knowledge, for educational and research institutions. This research, carried through within the Master Program in Information Science (PPGCI) of the school of Information Science/Federal University of Minas Gerais (UFMG), analyzes the use of the Portal dePeriódicos CAPES at the UFMG. The choice of this subject of study was due to the need of a better understanding of the object of study in the vision of its users. Few similar studies were found in the Brazilianscientific literature, even though the community of Information Science and CAPES, the institution responsible for maintenance of the Portal, were aware of its necessity. Moreover, this research provides important subsidies for improvement of this information retrieval system. The methodology used was a survey with questionnaires sent by email to the faculty faulty members in diverse fields of knowledge at UFMG. One hundred and fifty faculty faulty members distributed in eight areas of knowledge participated in this research. The questionnaire presents more than fifty questions related to the habits of the electronic journal users. It was possible to provide an overview of how the researchers of the UFMG make use of diverse digital instruments of work to carry through their research. The results were compared with statistics of access and use supplied by the staff of the Portal de Periódicos CAPES.